2007
DOI: 10.1038/modpathol.3800721
|View full text |Cite
|
Sign up to set email alerts
|

The ductal phenotypic expression of the E-cadherin/catenin complex in tubulolobular carcinoma of the breast: an immunohistochemical and clinicopathologic study

Abstract: Tubulolobular carcinoma is a type of mammary carcinoma that displays an admixture of invasive tubules and lobular-like cells. Previous reports have shown it to share clinical similarities to lobular carcinoma, whereas more recent studies have shown it to be E-cadherin positive. The aim of the current study was to further explore the immunophenotype of tubulolobular carcinoma, and to document its natural behavior. Nineteen cases of tubulolobular carcinoma and 10 cases each of tubular and lobular carcinoma were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 27 publications
3
41
1
Order By: Relevance
“…These resulting juxta-membrane α-catenin dimers bundle actin filaments and suppress actin assembly by inhibiting the Arp2/3 complex; under these conditions, cell-cell adhesion is high and cell migration/membrane dynamics are low. [47,51,86,[107][108][109][110][111][112][113][114][115][116][117][118][119] Histological type and growth [51], grade [47,112,117], stage [47], metastasis [47], survival [47,111] Survival [47], reduced more frequently in diffuse tumors [51] …”
Section: Discussionmentioning
confidence: 99%
“…These resulting juxta-membrane α-catenin dimers bundle actin filaments and suppress actin assembly by inhibiting the Arp2/3 complex; under these conditions, cell-cell adhesion is high and cell migration/membrane dynamics are low. [47,51,86,[107][108][109][110][111][112][113][114][115][116][117][118][119] Histological type and growth [51], grade [47,112,117], stage [47], metastasis [47], survival [47,111] Survival [47], reduced more frequently in diffuse tumors [51] …”
Section: Discussionmentioning
confidence: 99%
“…Also, they observed that these TLC tumors exhibited complete membranous staining with both α and β catenin compared to the cytoplasmic expression observed in lobular carcinomas. 3 The main differential diagnosis for TLC is Tubular carcinoma and Mixed ductal and lobular carcinoma. They are differentiated from each other by histopathological features.…”
Section: 45mentioning
confidence: 99%
“…They opted for a variant of lobular carcinoma on the basis of the cellular composition and an outcome worse than that of pure tubular carcinoma (although better than that of classical lobular carcinoma) [1]. Since then, a number of studies have evaluated this rare histological subtype of breast carcinoma, and most have concluded that it has overlapping features of both ductal and lobular cancers, but is better considered as a variant of ductal [2][3][4][5] or even tubular carcinoma [2]. Likewise, reports suggest that tubulolobular carcinomas are always [2,3,5] [5].…”
Section: Introductionmentioning
confidence: 99%